2015
DOI: 10.4238/2015.september.28.17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of genes involved in DNA repair influence treatment outcome in osteosarcoma

Abstract: ABSTRACT. We conducted a perspective study to investigate the role of ERCC1 (rs11615), ERCC2 (rs13181 and rs1799793), ERCC4 (rs1800067), and ERCC5 (rs17655) in NER pathway in the prognosis of osteosarcoma patients. In total, 146 osteosarcoma patients were recruited between 2008 and 2013. ERCC1 rs11615, ERCC2 rs13181 and rs1799793, ERCC4 rs1800067, and ERCC5 rs17655 gene polymorphisms were assessed by polymerase chain reaction-restriction fragment length polymorphism assay. By multivariate Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…An association with better event-free survival was reported for the GA/AA genotypes of ERCC2 rs1799793 polymorphism compared to GG genotype [ 69 ] and for patients with at least one polymorphic allele (GA/AA) [ 72 ]. In concordance with this evidence, other two studies showed that the AA genotype correlated with better response to chemotherapy and overall survival compared with the GG genotype [ 66 , 73 ].…”
Section: Pharmacogenetic and Pharmacogenomic Markers Associated Wisupporting
confidence: 72%
See 1 more Smart Citation
“…An association with better event-free survival was reported for the GA/AA genotypes of ERCC2 rs1799793 polymorphism compared to GG genotype [ 69 ] and for patients with at least one polymorphic allele (GA/AA) [ 72 ]. In concordance with this evidence, other two studies showed that the AA genotype correlated with better response to chemotherapy and overall survival compared with the GG genotype [ 66 , 73 ].…”
Section: Pharmacogenetic and Pharmacogenomic Markers Associated Wisupporting
confidence: 72%
“…The CC genotype of the ERCC1 rs11615 polymorphism was found to be associated with good response to cisplatin-based chemotherapy and better overall survival when compared to TT genotype [ 60 , 61 , 62 , 63 , 64 ]. However, other studies described the opposite evidence, being a better survival associated with the TT compared to CC genotype [ 65 , 66 ].…”
Section: Pharmacogenetic and Pharmacogenomic Markers Associated Wimentioning
confidence: 99%
“…Previous studies have examined the association between ERCC5rs2094258 and rs751402 polymorphisms and the development of certain malignancies, including breast and gastric cancers, salivary gland tumors, and oral squamous cell carcinoma (Duan et al, 2012;Yang et al, 2012;Zavras et al, 2012;Meng et al, 2013;Na et al, 2015;Wang et al, 2015). For instance, Duan et al (2012) and Yang et al (2012) both reported that these polymorphisms contribute to the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In another case-control investigation, Na et al (2015) assessed 324 breast cancer patients and 325 controls, and revealed that the ERCC5rs2094258 polymorphism may contribute to the development of this disease. However, in a Chinese study, Wang et al (2015) reported that ERCC5 genetic polymorphisms do not affect outcome of treatment for osteosarcoma. Thus, previous studies tend to suggest that ERCC5rs2094258 and rs751402 polymorphisms contribute to cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…[10] While there are also results suggested that the ERCC1 rs11615 TT genotype and ERCC2 rs1799793 AA genotype were associated with longer overall survival when compared with those with the wild-type genotype. [11] The conclusions on ERCC2 polymorphism were also inconsistent. Some studies suggested no association between ERCC2 rs13181 polymorphisms and overall survival in patients with osteosarcoma under cisplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%